Physiological, anatomical, and molecular responses of glanded and glandless cotton to chromium exposure - Samrana, Samrana; Ali, Abid; Hussain, Sayed; Ali, Hamid; Muhammad, Uzair; Abass, Kasim Sakran (Frontiers in Plant Science, 2026)
Cotton seeds are a major source of high-quality proteins and edible oil, but their utilization is limited due to gossypol toxicity to humans and animals. For better use of cotton as food and feed, several glandless cotton cultivars have been developed, which are susceptible to various biotic stresses. However, their resistance to abiotic stresses, i.e., heavy metals, has rarely been studied. In the current study, the effect of different doses of chromium (Cr)—0, 10, 50, and 100 μM—on the physiological, anatomical, and molecular aspects of cotton was investigated. Genotypic variation exists in the response of cotton to Cr stress. Current results revealed that Cr caused inhibition in leaf biomass and ultrastructure damage, showing large intercellular spaces, thick cell walls, distorted nucleus and chloroplast, and a ruptured nuclear membrane. Cr affected the biochemical system and resulted in the reduction of net photosynthesis rate by 69.7%, intercellular CO2 by 84%, and stomatal conductance by 68%. Thiobarbituric acid-reactive substances and H2O2 increased with increasing Cr concentration, with relatively higher levels in glanded cotton. The expression of genes (GhSOD, GhPOD, GhAPX, GhCAT) encoding antioxidant enzymes in the leaves was increased, helping to maintain the activity of antioxidant compounds. According to the results, it was observed that the antioxidant activity of GhSOD, upregulated 2.5-fold at 100 μM of Cr, plays a key role in mitigating Cr-induced oxidative stress. This study revealed the response mechanism of Cr stress in glanded and glandless cotton that might perform different mechanisms to cope with Cr toxicity.